2018
DOI: 10.1021/acs.biomac.8b00189
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Nanoparticle-Assisted Delivery of a Small Molecule-Drug Conjugate for Targeted Cancer Therapy

Abstract: Despite growing interest in targeted cancer therapy with small molecule drug conjugates (SMDCs), the short half-life of these conjugates in blood associated with their small size has limited their efficacy in cancer therapy. In this report, we propose a new approach for improving the antitumor efficacy of SMDCs based on nanoparticle-assisted delivery. Ideally, a nanoparticle-based delivery vehicle would prolong the half-life of an SMDC in blood and then release it in response to stimuli in the tumor microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
0
30
1
Order By: Relevance
“…In summary, we have developed HABN with unique anti-inflammatory properties and demonstrated its therapeutic efficacy after oral administration in a murine model of acute colitis (Figure 1a). While recent reports have explored systemic administration of polymermodified BR for disease treatments [39][40][41] , our work reported here demonstrate the promise of modulating intestinal barrier, microbiome, and immune responses with orally administered HABN. We show that HABN accumulated in DSS-damaged colonic epithelium and proinflammatory macrophages (Figures 1e-g) and upregulated the expression levels of tight junction-associated proteins and anti-microbial peptides in colon, while restoring intestinal barrier functions and protecting the epithelial layer against apoptosis (Figure 3a-e).…”
Section: Amelioration Of Colitis After Delayed Treatmentmentioning
confidence: 70%
“…In summary, we have developed HABN with unique anti-inflammatory properties and demonstrated its therapeutic efficacy after oral administration in a murine model of acute colitis (Figure 1a). While recent reports have explored systemic administration of polymermodified BR for disease treatments [39][40][41] , our work reported here demonstrate the promise of modulating intestinal barrier, microbiome, and immune responses with orally administered HABN. We show that HABN accumulated in DSS-damaged colonic epithelium and proinflammatory macrophages (Figures 1e-g) and upregulated the expression levels of tight junction-associated proteins and anti-microbial peptides in colon, while restoring intestinal barrier functions and protecting the epithelial layer against apoptosis (Figure 3a-e).…”
Section: Amelioration Of Colitis After Delayed Treatmentmentioning
confidence: 70%
“…The use of enhancers or nano/micro particulate carriers also represents a promising approach for peptide-targeted delivery (194,195). Interestingly, a recent report showed that bilirubin-based nanoparticles may represent a valid carrier option for many small peptides whose therapeutic efficacy is limited by their short circulation halflife (196) and this method could therefore be used for a more efficient delivery of BLVR-based peptides in vivo. Furthermore, BR-based nanoparticles have been tested in several diseases and conditions for their efficacy in tumor targeting and drug release (197)(198)(199)(200)(201)(202).…”
Section: Targeting Blvr In Cancer and Immune Diseasesmentioning
confidence: 99%
“…Due to the intrinsic properties of rosmarinic acid (RA) with poor water solubility and low bioavailability, Chung et al developed PEGylated RA-derived nanoparticles (RANPs) with a diameter of 63.5 ± 4.0 nm. 67 The PEGylated bioactive compound-derived nanoparticles not only achieved 100% RA loading capacity 68,69 but also achieved safer and longer RA circulation in the blood after intravenous injection. Therefore, RANPs can prolong the biological activity and have a higher probability of accumulating in the inflamed tissues where the vascular permeability is increased.…”
Section: Passive Targetingmentioning
confidence: 99%